Distribution Law of In Situ Stress and Its Engineering Application in Gateroad Maintenance: A Case Study - Guangchao Zhang; You Li; Guangzhe Tao; Miao Chen; Ruihua Xu; Hanqing Guo; Devkota Bidit; Guanglei Zhou; Zhi Qu; Hao Zuo (Geofluids)
In this study, the stress relief method of hollow inclusion and mathematical-statistical analysis are used to study the in situ stress distribution law of the Guotun coal mine, and the optimization strategy of roadway support is put forward. The test site is located in the city of Heze, Shandong Province, China. The main conclusions included the following: (1) among the three large-scale tectonic movements experienced by the Guotun coal mine, the middle Yanshan period has the strongest impact on it. According to the geological evolution process, it is preliminarily inferred that the maximum principal stress direction of the Guotun coal mine is northwest by west to southeast by east (NWW∼SEE). (2) Compared with the surrounding mines, the average value of the maximum principal stress in the Guotun coal mine is slightly higher, and there is a significant difference in the direction of in situ stress. The arc structure within the mine is the main reason for the deflection of the stress direction. (3) The lateral pressure coefficients KH, Kh, and Kav show a nonlinear distribution with increased depth, and the three coefficients have a decreasing trend. The value of the stress gradient in the Guotun coal mine is greater when it is compared with the surrounding mines. (4) Field tests show that the new strategy proposed in this study is effective, which provides a good reference for engineering practice under similar geological conditions.